SCREENING OF TOTAL FLAVONOID CONTENTS IN LOCAL ACCESSIONS OF CENTELLA ASIATICA AS MEDICINAL HERB - Moghaddam, S.; Jaafar, H.; Ibrahim, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Centella asiatica is a small herbaceous annual plant of the family Apiaceae, locally known as Pegaga in Malaysia. Common names include Gotu Kola, Asiatic Pennywort, Antanan, and Brahmi. It is one of the most common medicinal plants used by diverse ancient cultures and has been widely used as health food and in cosmetic industries. Flavonoid compounds, especially quercetin have anti-tumor activity and it is clear that Centella asiatica has higher flavonols (quercetin) and flavanals (naringin) content compared with vegetables and fruits. A study was conducted to analyse the total flavonoid contents (TFC) in 8 local accessions. Significant differences were observed both in their morphological characters and total flavonoid contents (TFC), detected at a range of 760.36µg/ml to 1512.27µg/ml dry weight of whole plant. Highest TFC was recorded in A2 (1512.27µg/ml) and lowest in A3 (760.36µg/ml). Analysis on different parts of the plant also revealed that leaf tissue contains the highest flavonoid, followed by petiole and root. Total flavonoid content in the leaf was highest in A2 (1309µg/ml) and lowest in A3 (519µg/ml). However, A3 also recorded the highest TFC in the petiole (194µg/ml). Time to harvest was observed to be an important factor for accumulation of TFC in the plant and S3 (6 weeks after planting) was recorded to be the best for all accessions. Information on morphological, chemical and growth characteristics of these accessions can be further applied in micropropagation and mutation breeding programmes to select for desirable traits of fast growth, high biomass and flavonoid content for commercialisation.